Kandungan Hemiselulosa pada Serat Kasar Eceng Gondok (Eichhornia crassipes) - Fatmawati Fatmawati; Ahmad Syauqi; Majida Ramadhan (Jurnal SAINS ALAMI (Known Nature), 2023)
Water hyacinths can grow quickly, so efforts are needed to deal with them so as not to disturb and damage the environment. The cell wall of hyacinth plants contains lignocellulose. The purpose of this study is to determine the quantity of hemicellulose molecules from the results of hydrolysis on the presence of a component of the crude fiber of hyacinth (Eichhornia crassipes). The methods used in this study were the Wendee crude fiber analysis method and the Chesson-Datta method of hemicellulose hydrolysis. The study used quantitative descriptive methods. The results of the analysis of hyacinth crude fiber in every 1gram of dried hyacinth powder contain an average crude fiber weight contained minerals in the leaves of 30.9% and 48.6% in the roots. Hydrolysis of hemicellulose obtained the average hemicellulose contained in hyacinth leaves 11.2% and roots 19.7%. Keywords: Hyacinth, Crude fiber, Hemicellulose ABSTRAK Eceng gondok dapat tumbuh dengan cepat, sehingga diperlukan upaya untuk menanganinya agar tidak mengganggu dan merusak lingkungan. Dinding sel tanaman eceng gondok mengandung lignoselulosa. Tujuan dari penelitian ini untuk mengetahui kuantitas molekul hemiselulosa dari hasil hidrolisis pada keberadaan komponen serat kasar eceng gondok (Eichhornia crassipes). Metode yang digunakan dalam penelitian ini yaitu metode analisis serat kasar Wendee dan hidrolisis hemiselulosa metode Chesson-Datta. Penelitian menggunakan metode deskriptif kuantitatif. Hasil analisis serat kasar eceng gondok dalam tiap 1gram serbuk eceng gondok kering mengandung rata-rata berat serat kasar terkandung mineral pada daun 30.9% dan 48,6% pada akar. Hidrolisis hemiselulosa didapatkan rata-rata hemiselulosa yang terkandung dalam daun eceng gondok 11,2% dan akar 19,7%. Kata kunci: Eceng gondok, Serak Kasar, Hemiselulosa